2019
DOI: 10.1111/imm.13090
|View full text |Cite
|
Sign up to set email alerts
|

Adipocytokines leptin and adiponectin function as mast cell activity modulators

Abstract: Summary A growing body of data indicates that adipocytokines, including leptin and adiponectin, are critical components not only of metabolic regulation but also of the immune system, mainly by influencing the activity of cells participating in immunological and inflammatory processes. As mast cells (MCs) are the key players in the course of those mechanisms, this study aimed to evaluate the impact of leptin and adiponectin on some aspects of MC activity. We documented that in vivo differentiated mature tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 58 publications
(111 reference statements)
0
21
0
Order By: Relevance
“…Moreover, adiponectin exerts an antioxidant (oxidative and nitrative stress) activity that is AMPK-independent and that is largely mediated via PKA-dependent NF-κB inhibition ( 52 ). Importantly, adiponectin modulates the activity of several immune cells in the AT including macrophages ( 53 , 54 ), eosinophils ( 55 ), and mast cells ( 56 ). Indeed, profound mechanistic frameworks for this modulation are still lacking and require further investigation.…”
Section: Obesity At Inflammation and The Metabolic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, adiponectin exerts an antioxidant (oxidative and nitrative stress) activity that is AMPK-independent and that is largely mediated via PKA-dependent NF-κB inhibition ( 52 ). Importantly, adiponectin modulates the activity of several immune cells in the AT including macrophages ( 53 , 54 ), eosinophils ( 55 ), and mast cells ( 56 ). Indeed, profound mechanistic frameworks for this modulation are still lacking and require further investigation.…”
Section: Obesity At Inflammation and The Metabolic Syndromementioning
confidence: 99%
“…Indeed, these metabolic processes regulate MCs inflammatory cytokines and ROS production and IGE-mediated degranulation ( 203 , 204 , 230 ). A role for adipokines in the regulation of MC function has been recently revealed ( 56 ). Leptin and adiponectin were shown to exert opposite effects on MC polarization to promote a pro-inflammatory or an anti-inflammatory cytokine profile, respectively.…”
Section: Metabolic Regulation and Adaptation Of Tissue Resident And Imentioning
confidence: 99%
“…In this issue, we report on a study that has identified new roles for leptin and adiponectin in controlling responses from mast cells . Mast cells from the rat peritoneal cavity were found to express the receptors for both leptin and adiponectin, and to respond to these adipokines by producing cytokines and reactive oxygen species.…”
mentioning
confidence: 99%
“…The expression of adiponectin receptors has been also reported in immune cells, such as monocytes, 18 neutrophils 16 and mast cells. 19 Although both adiponectin receptors are found on the surface of natural killer (NK) cells, natural killer T (NKT) cells, B cells, CD4 + and CD8 + T lymphocytes, all these cells predominantly express AdipoR2. 20 Resistin is another prominent adipokine that together with RELMα, RELMβ and RELMγ belongs to the resistin-like molecule (RELM) family.…”
mentioning
confidence: 99%